Classroom Management Problems Faced by Pre-Service Teachers Study Case: At Senior High School 1 of Plumbon - afiah, devi siti (Universitas Swadaya Gunung Jati, 2018)
This research studied about classroom management problems faced by pre-service teacher. Pre-service teacher is student teachers before they have under taken any teaching. Before they are graudate, they have to accomplish teacher training subject. When they come to schools to teach students, they find so many new things, such as; the real instructional devices, students’s characters of senior high school, students’ responses in learning process. In this study, the writer investigated the students’ responses in learning process, and it become challanging for pre-service teacher to solve bed students’ responses. There are some classroom mangement problems that pre-service teacher faced, they are: students always lots of students played mobile phone, been lazy, had chat, been passive students during learning process.